Fiqh Principles and the Legitimacy of Indonesia's Isbat Session System - Annisa Nurfadilah; Ahmad Adib Rofiuddin; Muh. Rasywan Syarif (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
This study aims to examine the sharia legitimacy of the Isbat Session in determining the beginning of the lunar month in Indonesia through the perspective of the fiqh principle of Tasharruf al-Imam ‘ala al-Ra’iyyah Manutun bi al-Maslahah. The focus of the study is to analyze the normative basis of this principle as a basis for state authority and to test the effectiveness of its implementation in reconciling differences in hisab-rukyat and realizing the welfare of the people. The study uses empirical qualitative methods with content analysis and critical discourse analysis approaches. Primary data includes official documents from the Ministry of Religious Affairs regarding the results of the Isbat Session for the 2015–2025 period and public responses, while secondary data are sourced from fiqh literature, journals, and related books. The research findings indicate that the Isbat Session has strong sharia legitimacy based on the principle of tasharruf al-imam, where the state acts as ulil amri who ensures the realization of public welfare through collective decisions. Empirically, 82% of the Isbat Session decisions were successfully agreed upon by the government, NU, and Muhammadiyah, proving the forum's effectiveness as a unifying instrument. However, 18% of the differences that occurred—particularly with Muhammadiyah—were caused by fundamental methodological differences between rukyat bil fi'li (NU) and hisab wujudul hilal (Muhammadiyah). This study concludes that the Isbat Session is a form of Islamic jurisprudence that is valid according to sharia and effective in creating legal certainty and social stability, although further efforts are still needed to embrace the remaining methodological differences.